Effects of deep brain stimulation of the subthalamic nucleus on inhibitory and executive control over prepotent responses in Parkinson's disease - Jahanshahi, Marjan (Frontiers in Systems Neuroscience, 2013)
Inhibition of inappropriate, habitual or prepotent responses is an essential component of executive control and a cornerstone of self-control. Via the hyperdirect pathway, the subthalamic nucleus (STN) receives inputs from frontal areas involved in inhibition and executive control. Evidence is reviewed from our own work and the literature suggesting that in Parkinson’s disease (PD), deep brain stimulation (DBS) of the STN has an impact on executive control during attention-demanding tasks or in situations of conflict when habitual or prepotent responses have to be inhibited. These results support a role for the STN in an inter-related set of processes: switching from automatic to controlled processing, inhibitory and executive control, adjusting response thresholds and influencing speed-accuracy trade-offs. Such STN DBS-induced deficits in inhibitory and executive control may contribute to some of the psychiatric problems experienced by a proportion of operated cases after STN DBS surgery in PD. However, as no direct evidence for such a link is currently available, there is a need to provide direct evidence for such a link between STN DBS-induced deficits in inhibitory and executive control and post-surgical psychiatric complications experienced by operated patients.